Hippocampal Involvement With Vigabatrin-Related MRI Signal Abnormalities in Patients With Infantile Spasms: A Novel Finding. (June 2021) - Harini, Chellamani; Yuskaitis, Christopher J.; Libenson, Mark H.; Yang, Edward; DeLeo, Michelle; Zhang, Bo; Mysak, Kate; Marti, Candice; Peters, Jurriaan M.; Bergin, Ann Marie; Pearl, Phillip L.; Prabhu, Sanjay P.
Background: In a subset of infants exhibiting typical vigabatrin-related magnetic resonance imaging (MRI) changes, the authors observed additional hippocampal signal abnormalities. The authors investigated occurrence and significance of additional signal abnormalities. Methods: A retrospective review of infantile spasms patients with typical vigabatrin-related MRI abnormalities was performed. Atypical features included signal changes unilaterally or at previously unreported sites. Comparisons were made between patients with and without atypical features. Results: In all, 26/55 (47%) exhibited typical vigabatrin-related MRI changes, with additional signal abnormalities in the hippocampi in 6 of 26. On follow-up, evolution of hippocampal signal changes paralleled changes at typical locations in 4 patients. Two patients, clinically well, without follow-up MRI. Patients with and without additional hippocampal signal changes did not differ with respect to clinical factors, including seizure status. One patient had unilateral thalamic/cerebral peduncle signal abnormality along with typical vigabatrin changes. Conclusions: Hippocampal changes seen in subset of patients with typical vigabatrin-related changes may be attributable to vigabatrin exposure in the appropriate circumstance.